1975
DOI: 10.1070/qe1975v005n01abeh010821
|View full text |Cite
|
Sign up to set email alerts
|

Emission of λ≈2 μ stimulated radiation by holmium in aluminum holmium garnet crystals

Abstract: The formula whch has been proposed by Chandrasekhar to express the dependence of the rotatory power on wavelength has the form where Ki is a constant and A, is the characteristlc wavelength. This quadratic formula was prevlously denved for crystals with space group of symmetry Dt or its enantiomorphous D:. However, Chandrasekhar and other authors have shown that this formula may be used also for crystals which belong to other groups of In this paper we have removed certain simplifying assumptlons of Chan-symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…The (Lu 1/6 Y 1/6 Ho 1/6 Dy 1/6 Tb 1/6 Gd 1/6 ) 3 Al 5 O 12 crystals have a single garnet phase, as confirmed by the powder XRD patterns in Figure 3; reference YAG reflection peaks 39 are also plotted for height. Assuming a homogeneous mixture of the six REs throughout the whole crystal, one would expect the lattice parameter of the multicomponent composition to be close to the average taken from the lattice parameters of the corresponding one-component REAG, namely, LuAG, 40 YAG, 40 HoAG, 29 DyAG, 41 TbAG, 42 and GdAG. 40 Figure 4 includes the literature values of the lattice parameters of single-REAG as a function of rare-earth ionic radius for the 3+ oxidation state and coordination number VIII 22 (black circles).…”
Section: Resultsmentioning
confidence: 99%
“…The (Lu 1/6 Y 1/6 Ho 1/6 Dy 1/6 Tb 1/6 Gd 1/6 ) 3 Al 5 O 12 crystals have a single garnet phase, as confirmed by the powder XRD patterns in Figure 3; reference YAG reflection peaks 39 are also plotted for height. Assuming a homogeneous mixture of the six REs throughout the whole crystal, one would expect the lattice parameter of the multicomponent composition to be close to the average taken from the lattice parameters of the corresponding one-component REAG, namely, LuAG, 40 YAG, 40 HoAG, 29 DyAG, 41 TbAG, 42 and GdAG. 40 Figure 4 includes the literature values of the lattice parameters of single-REAG as a function of rare-earth ionic radius for the 3+ oxidation state and coordination number VIII 22 (black circles).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 1:1 compounds (LnAlO 3 ) based on large rare earths are stable compounds, while stability drastically decreases upon moving to smaller rare earths [4]. The possibility of formation of the end-member, LuAlO 3 , under normal pressures was being even denied until the work [5], in which growth of LuAlO 3 single crystals by Czochralski method was reported. In order to reveal the conditions of formation of the perovskite phase, phase equilibria in the Lu 2 O 3 -Al 2 O 3 system were studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The LuAlO 3 compound was obtained by crystallization of undercooled melts [5,6]. Studies of thermal stability of LuAlO 3 single crystals grown by Czochralski techniques have shown that LuAlO 3 decomposes separating Lu 3 Al 5 O 12 and Lu 2 O 3 phases, when heated above 1000 1C; the phases observed upon heating to the melting point were Lu 4 Al 2 O 9 and Lu 3 Al 5 O 12 [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…9). The disposition of the energy levels and luminescence intensity properties of known generating Tm 3+ -doped crystals (Tables 1, 3, 5, and 6) allow the creation of cascade and cross-cascade [75,202,203] as well as cross-relaxation [195] laser schemes. It is also known that tunable SE in the vacuum UV region can be excited at the interconfiguration 4f 11 5d 1 -4f 12 ed-allowed transition of Tm 3+ ions in several anisotropic fluoride crystals [204].…”
Section: Laser Channels Of Tm 3+ and Yb 3+ Ionsmentioning
confidence: 99%